Overexpressed MAGP1 Is Associated With a Poor Prognosis and Promotes Cell Migration and Invasion in Gastric Cancer - Wu, Mengjie; Ding, Yongfeng; Jiang, Xiaoxia; Chen, Yanyan; Wu, Nan; Li, Linrong; Wang, Haiyong; Huang, Yingying; Xu, Nong; Teng, Lisong (Frontiers in Oncology, 2020)
Gastric cancer (GC) frequently occurs and has a high mortality rate. However, the underlying mechanism of GC progression is not very clear. The aim of this study is to reveal the inherent molecular mechanism and develop potential therapeutic targets for advanced GC. By comparing the transcriptomes between metastatic and early stage tumors, we identified a set of putative progression-associated genes, of which the microfibril-associated glycoprotein 1 (MAGP1), an extracellular matrix (ECM)-related protein, was found upregulated in GC tissues and high MAGP1 expression was associated with aggressive clinicopathologic features. Furthermore, the multivariate Cox regression analysis showed that high MAGP1 expression was an independent predictor of poor prognosis (HR = 2.37, 1.07-5.24; P = 0.033). In vitro functional assays, we found that MAGP1 promoted the migration and invasion ability of GC cell. In addition, we identified co-expressed genes with MAGP1 and found that these genes were largely enriched in focal adhesion and PI3K-Akt pathways. The subsequent western blot analysis verified that MAGP1 overexpression enhanced the phosphorylation of FAK, AKT, mTOR, whereas MAGP1 knockdown suppressed the activation of FAK, AKT, mTOR. Meanwhile, the AKT inhibitor suppressed the phosphorylation of AKT, FAK, and mTOR in recMAGP1-treated AGS cells. Taken together, MAGP1 is a promising prognostic marker and potential therapeutic target for advanced GC.